PENILAIAN KELAYAKAN INVESTASI PADA WARALABA INDOMARET - Murni, Yanti; M., Hirdinis (L2Dikti Wilayah III, 2018)
Indomaret outlets in Indonesia has reached 5425 outlets spread out in the city of Jabodetabek area, West Java, East Java, Central Java, Yogyakarta, Bali and Lampung and some other areas. The assessment of investments using Net Present Value (NPV) of financial data for the last 5 (five) years obtained the calculation result is positive. This means that the investment can be forwarded. The purpose of this research is to find out the feasibility of investing in a franchise Indomaret. The research methods used are case studies. Data obtained from the interviews and the examination of documents. The processing and data analysis done with the method of valuation of the investment. The results of the study are: (1) after an assessment of the investment by the method of Net Present Value (NPV) of financial data for the last 5 (five) years obtained the calculation result is positive. This means that investments can be forwarded, (2) with assessment methods according to the investment Payback Period Method, investment funds have been implanted can return in less than the time of the contract that is 5 (five) years, the investment can be returned within 3 years and 5 months.